Surgical treatment of rhegmatogenous retinal detachment using air tamponade and C3F8 gas tamponade - D.O. Shkvorchenko; E.S. Khrisanfova; D.G. Uzunyan (Офтальмохирургия)
Relevance. Retinal detachment is a serious disease, that requires immediate surgical treatment. If there is no doubt about the need for urgent surgical treatment, then the question of choosing tamponing substance after retinal immobilization remains open. Often there are no clear criteria for choosing one or another tamponing substance and this issue is determined by the preference of the surgeon. Purpose. To evaluate effectiveness and compare result of surgical treatment of rhegmatogenous retinal detachment using air and C3F8 gas tamponade. Material and methods. Surgical treatment of 43 patients diagnosed with rhegmatogenous retinal detachment was performed and the results of treatment were evaluated. All patients were divided into 2 groups. The first group included 23 patients with the best corrected visual acuity 0.01–0.9 (±0.06). Surgical treatment of patients from this group was completed with sterile air tamponade. The second group included 20 patients with the best corrected visual acuity of 0.01–0.8 (±0.08). Surgical treatment was completed with a 2.5% C3F8 gas tamponade. Results. By the third month of follow-up after surgical treatment B-scan data showed no pathology in all cases of both groups. Visual acuity in group 1 was 0.55-1.0 (±0.063), in group 2 was 0.45–1.0 (±0.061). Light sensitivity in group 1 was 24.5–30.1 (±0.34) dB, in group 2 was 23.1–27.7 (±0.41) dB. Conclusion. Given the comparable clinical results, air tamponade in surgery for rhegmatogenous retinal detachment is preferable than using 2.5% C3F8 gas tamponade.